A time-space conversion method for material synthesis research - Yuting Hou (Elsevier, 2021)
Summary: Research on material synthesis is mostly performed through batch by batch testing with each corresponding to a set of parameters and a reaction time. Concurrent experiments that allow for multiple loadings throughout an inhomogeneous reaction zone provide a way to obtain high-throughput results. Here, a time-space conversion method is proposed. By sequentially passing a number of identical objects through a reaction zone, a significant diversity of reactions in one batch can be achieved depending on the spatial distribution and changes with time of the reaction zone. In particular, when the reaction zone is steady, the evolution of a reaction can be associated with the objects at their corresponding reaction stage. This greatly improves the efficiency and accuracy of research on material synthesis kinetics. This method may initiate a new wave of material synthesis research and accelerate the development of material science.